FUNGSI JOSHI NO DALAM BUKU CERITA NEZUMI TO KUJIRA TERJEMAHAN SETA TEIJIYAKU - sabih asyari; Hendri Zalman; Meira Anggia Putri (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2020)
AbstractThis research aimed to know function of Joshi “no” in the story Nezumi To Kujira by William Steig. This research used qualitative research method which Analyze Descriptive. Research of Data used the sentence Joshi “no” , on the story Nezumi To Kujira by William Steig, the finding of the data is 40 sentences. The result of the research, found 4 function from 10 theory of joshi “no” function. Combine two noun together 31 data, combine two part of sentence 3 data, giving example or imagery 1 data, and  stating the object or possession there are 5 data.Keywords: Function, Joshi no